Faktor Penganggaran, Penatausahaan, dan Aplikasi Akuntansi Terhadap Kualitas Laporan Keuangan Studi Kasus pada Rumah Sakit Mata Makassar - Caesaria Febriastri, Safira; Wikan Kinasih, Hayu (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of budgeting, administration, and accounting applications on the quality of financial reports at the Makassar Eye Hospital. This type of research uses a quantitative approach with data collection through questionnaires and direct surveys. The sampling was conducted usiang a purposive sampling method. The population that became the object of research was employees who were directly involved in managing the hospital's accounting information system, totaling 30 employees. The analysis method applied is Partial Least Squares Structural Equation Modeling (PLS-SEM) with software SmartPLS.. The results of the data analysis show that budgeting, administration and financial applications exert a significant impact on the quality of financial statements. The model explains is 0.812 or 81,2% of, while 18,8% accounted for by variables not examined in this research.